Global banking, trade, and the international transmission of the great recession - Born, Alexandra; Enders, Zeno (CESifo working papers, 2018)
The global financial crisis of 2007-2009 spread through different channels from its origin in the United States to large parts of the world. In this paper we explore the financial and the trade channel in a unified framework and quantify their relative importance for this transmission. Specifically, we employ a DSGE model of an open economy with an internationally operating banking sector. We investigate the transmission of the crisis via the collapse of export demand and through losses in the value of cross-border asset holdings. Calibrated to German data, the model predicts the trade channel to be twice as important for the transmission of the crisis than the financial channel. In the UK, the latter dominates due to higher foreign-asset holdings, which, at the same time, serve as an automatic stabilizer in case of plummeting foreign demand. The transmission via the financial channel triggers a much longer-lasting recession relative to the trade channel, resulting in larger cumulated output losses and a prolonged crisis particularly in the UK. Stricter enforcement of bank capital requirements would have deepened the initial slump while simultaneously speeding up the recovery. The effects of higher capital requirements depend on the way banks' balance sheets adjust to this intervention.
Keywords: Graue Literatur